Characterization of Wear Patterns in Gun Barrel’s Throat Region using Forensic Microscope: Insights into Long-term Effects of High-Pressure Gas Exposure - Ningal, Jevie B (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
This research aims to explore the damage sustained by the gun barrel's throat region over a long period of use, shedding light on the wear characteristics, and providing valuable insights into the long-term effects of high-pressure gas exposure during firing. To achieve this objective, the appearance of the gun barrel's throat region was characterized using forensic microscopy techniques. Visual and microscopic examinations were conducted on five (5) gun barrels with ten years or less of service usage and five (5) gun barrels with over ten years of service usage from the Philippine National Police to assess the degree of wear in the barrel’s throat region. The findings revealed varying degrees of wear in the barrel throat regions. Firearms with 10 years or less of service usage exhibited moderate corrosion, narrow cracks, and minimal soot particle presence while firearms with over 10 years of service usage showed severe corrosion, deep cracks, scattered potholes, superficial scraped surfaces, and heavy soot particle presence. This research contributes to the understanding of barrel performance, maintenance, and potential hazards associated with aging firearms, thus providing novel insights into the long-term effects of high-pressure gas exposure during firing. By examining the changes in material properties and surface roughness of the gun barrel’s throat region, this study seeks to improve the understanding of how repeated firing impacts gun barrel performance and longevity. This, in turn, may aid in developing future maintenance practices to enhance firearm durability and safety.